"Comfort-foods" chronic intake has different behavioral and neurobiological effects in male rats exposed or not to early-life stress. (6th June 2019) - Cunha, ACA; Dalle Molle, R; Laureano, DP; Reis, AR; Corrêa, C; Matte, US; Silveira, PP; Machado, TD
Abstract: The ability of "comfort-food" (CF) diet to revert long-term effects of early-life stress (ELS) is less well known. The objective of this study was to verify if the chronic exposure to CF diet in animals submitted to ELS could relief the stress response at behavioral, neuroendocrine, and neurobiochemical levels, via differences in glucocorticoid receptors expression in brain areas involved in the stress response. From the second day of life, litters of Wistar rats and their mothers were submitted to the reduced nesting material protocol (ELS). In adult life, ELS and a control group were exposed chronically to two diet schemes: standard rat chow only or both "CF" diet, containing fat (34%) and sugar (20%) and a diet similar to the standard diet. Anxiety-like behavior, neuroendocrine response stress, leptin, GR, SOCS-3, pSTAT3, and the abdominal fat were evaluated. The anxiety-like behavior results showed that ELS group when exposed to comfort food were not different from the others groups. Chronic exposure to CF diet induced an anxiety-like behavior in the control group. Groups chronically exposed to CF diet had lower levels of corticosterone over time independent of the neonatal group. The ELS group exposed to the "CF" diet had higher levels of hippocampal GR, lower levels of hypothalamic SOCS-3 and greater accumulation of abdominal fat. Chronic CF diet consumption is able to reduce corticosterone levels independent of the neonatal history, but is associated with anxiety-like behavior in animals without previous history of trauma. Metabolic disturbances like increased adiposity and altered SOCS-3 seem to be a result of multiple insults (neonatal trauma followed by chronic CF diet). We highlight that the Control-chow and ELS-chow data were previously published, and are included in this study for comparative analysis.